2004
DOI: 10.4070/kcj.2004.34.9.874
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Hypertension, Insulin Resistance, and Metabolic Syndrome in the Serum Uric Acid Level

Abstract: Background and Objectives:The relationship between serum uric acid and metabolic syndrome variables has not been reported in Korea. Therefore, whether the circulating levels of serum uric acid are independently related to hypertension, insulin resistance and the variables of metabolic syndrome were assessed. Subjects and Methods:A total of 53,477 health screen examinees were enrolled and divided into four groups (Quartile 1:<4.2 mg/dL, Quartile 2:4.2-5.29 mg/dL, Quartile 3:5.3-6.29 mg/dL, Quartile 4:>6.29 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
5
2
1
Order By: Relevance
“…RBP4 level is currently known to be independently associated with uric acid level in patients with type 2 diabetes mellitus 15). Our data showed that serum RBP4 levels were elevated in the HTN with MS group, but was not significantly different than in the HTN without MS group (p=0.106).…”
Section: Discussioncontrasting
confidence: 44%
“…RBP4 level is currently known to be independently associated with uric acid level in patients with type 2 diabetes mellitus 15). Our data showed that serum RBP4 levels were elevated in the HTN with MS group, but was not significantly different than in the HTN without MS group (p=0.106).…”
Section: Discussioncontrasting
confidence: 44%
“…There is a study that uric acid is related to the components of the metabolic syndrome in the Korean population. ( 23 )…”
Section: Discussionmentioning
confidence: 99%
“…2)3)9)11)15) 16) SUA levels rise steadily with age, with the levels in men beginning to rise during puberty. The SUA levels in women remain lower until menopause, possibly due to the effect of estrogen.…”
Section: )6)mentioning
confidence: 99%